ANALISIS PELAKSANAAN PEMILIHAN KETUA PEMUDA DI DESA TANJUNG PAUH KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Putra Andres Pratama; Sri Erlinda; Supentri Supentri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research is done by changing the way of choosing youth chairman in Tanjung Pauh Village formerly implemented by Deliberation but now it is done by direct election. The formulation problem of this research is what factors caused the change of youth election from the way of musyawarah to direct election and how the election of youth chairman in Tanjung Pauh Village and in election of youth chairman in Tanjung Pauh Village using Democracy principles. The population of this research is the people of Tanjung Pauh Village as many as 2,099 people, the sample is 80 people using the technique of taking proposive sampling. Data collection techniques are observation, questionnaires, interviews and documentation. The results of this study indicate that the factors lead to changes in the way of elections from direct consensus deliberation discussions are the effects of musyawarah discussed using a very long time, new problems arise that sometimes out of the topic of discussion, participants became passive and decisions are often ignored. In the election of youth chairman in Tanjung Pauh Village, implemented based on the principle of direct, public, free, secret, voters are villagers Tanjung pauh, voters have only one vote to elect the youth chairman, it is not allowed to late, election system using voting technique, voter can not be represented, and voters who have chosen to get a mark are ink on hand. In the election of youth chiefs in Tanjung Pauh Village using democratic principles directly, publicly, freely, secretly, honestly, fairly, elections are implemented democratically, procedurally, transparently, accountably, the government maintains integrity and neutrality, and protects and maintains equal rights voters with a one-vote principle have the same value.Keyword : Election, youth leader, democracy.